PRE WEANING GROWTH OF BALI CALVES AT BALAI PEMBIBITAN TERNAK UNGGUL SAPI BALI - Luis Tavares; Endang Baliarti; Sigit Bintara (Buletin Peternakan, 2012)
Balai Pembibitan Ternak Unggul is a breeding center established by the Government of Indonesia (GOI) to perform preservation, breeding, breeding stock production and development, and also the distribution of breeding stock of Excellent Bali cattle at national level. In the production of excellent breeding stock through the performance test and progeny test. Pre-weaning growth is one of the important indicators for the population growth. The study was aimed to identify the pre-weaning calf growth rate of Bali cattle in 2010-2011, born from performance-test-passing-dams that were collectively reared with progeny-test-passing sires. Materials used were 84 pre-weaning Bali calves. This was a survey method-based descriptive analysis research. The results showed that in terms of the performance of pre-weaning growth, the birth weights of male and female calves were 18.37±1.65 kg and 18.27±1.29 kg, respectively. The weaning weights of male and female calves were 93.53±21.00 kg and 87.66±12.04 kg, respectively, with weaning time of 205 days. The average of daily weight gain (ADG) were 0.37±0.10 kg/head/day (male) and 0,34±0,06 kg/head/day (female). It was concluded that the pre-weaning calf growth rate of Bali cattle at the BPTU Bali in 2010-2011 were moderately high since they were born from the dams and the sires passing the performance test and progeny test.(Keywords: Pre-weaning growth, Bali cattle)